IMPACT ANALYSIS OF THE ZAKAT, INFAQ AND SHADAQAH FUNDS DISTRIBUTION TO THE POVERTY LEVEL OF MUSTAHIK BY USING CIBEST METHOD - Khairul Rijal; Ahmad Zainuri; Peny Cahaya Azwari (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
Poverty in South Sumatra is very high, so special care must be taken to reduce the problem, inversely proportional to the high enough zakat potential. The regulation on zakat using the payroll system from the salary of every government employee has been implemented. This regulation has a positive impact on collecting zakat funds in South Sumatra, but the position of zakat in helping the government to reduce poverty in this province needs to be explored further in scientific work, a case study of 100 zakat recipients managed by the national board of zakat (BAZNAS) by analyzing the impact of the distribution of zakat, infaq and shadaqah in reducing poverty based on the CIBEST method. This shows that the distribution of zakat, infaq and shadaqah carried out by BAZNAS can significantly reduce povertythat the provision of zakat funds in the form of venture capital was on target, able to increase the welfare index by 55.84% then the spiritual index increased to 4,026 which was previously only 3,870 and the mustahik income and reduced the poverty index both materially decreased by 27.77% and the absolute poverty index decreased by 100 % or no more categorized as material and spiritual poor.